NLR family pyrin domain containing 3 (NLRP3) and caspase 1 (CASP1) modulation by intracellular Cl– concentration - Clauzure, Mariangeles (2021)
The impairment of the cystic fibrosis transmembrane conductance regulator (CFTR) activity induces intracellular chloride (Cl–) accumulation. The anion Cl–, acting as a second messenger, stimulates the secretion of interleukin-1β (IL-1β), which starts an autocrine positive feedback loop. Here, we show that NLR family pyrin domain containing 3 (NLRP3) and caspase 1 (CASP1) are indirectly modulated by the intracellular Cl– concentration, showing maximal expression and activity at 75 mM Cl–, in the presence of the ionophores nigericin and tributyltin. The expression of PYD and CARD domain containing (PYCARD/ASC) remained constant from 0 to 125 mM Cl–. The CASP1 inhibitor VX-765 and the NLRP3 inflammasome inhibitor MCC950 completely blocked the Cl–-stimulated IL-1β mRNA expression and partially the IL-1β secretion. DCF fluorescence (cellular reactive oxygen species, cROS) and MitoSOX fluorescence (mitochondrial ROS, mtROS) also showed maximal ROS levels at 75 mM Cl–, a response strongly inhibited by the ROS scavenger N-acetyl-L-cysteine (NAC) or the NADPH oxidase (NOX) inhibitor GKT137831. These inhibitors also affected CASP1 and NLRP3 mRNA and protein expression. More importantly, the serum/glucocorticoid regulated kinase 1 (SGK1) inhibitor GSK650394, or its shRNAs, completely abrogated the IL-1β mRNA response to Cl– and the IL-1β secretion, interrupting the autocrine IL-1β loop. The results suggest that Cl– effects are mediated by SGK1, in which under Cl– modulation stimulates the secretion of mature IL-1β, in turn, responsible for the upregulation of ROS, CASP1, NLRP3 and IL-1β itself, through autocrine signalling.